Site-selective immobilization of functionalized DNA origami on nanopatterned Teflon AF - Shaali, M; Woller, J; Johansson, P; Hannestad, J; De Battice, L; Aissaoui, N; Brown, T; El-Sagheer, A; Kubatkin, S; Lara-Avila, S; Albinsson, B; Jesorka, A (RSC Publishing, 2017)
We demonstrate the use of arrays of Teflon AF nanopillars for directing the assembly of single rectangular DNA origami scaffolds, functionalized with covalently linked fluorophore molecules, in defined positions on patterned surfaces. This is achieved by introducing Teflon AF as a non-amplified negative e-beam resist, which is exposed and chemically developed to generate arrays of hydrophobic nanopillars with a minimum feature size 40 nm. Binding of the DNA origami to the pillars is facilitated by porphyrin moieties that act as hydrophobic molecular anchors, reaching 80% coverage of the available sites. This combination of top-down lithography and bottom-up self assembly is an efficient means of fabricating hierarchically structured bio-nanointerfaces in which the positioning of functional units is precisely controlled on the molecular scale inside the DNA assembly, and on the nanoscale at pre-designed locations on the substrate.